pVHL(19) is a biologically active product of the von Hippel–Lindau gene arising from internal translation initiation - Iliopoulos, Othon (National Academy of Sciences, 1998)
The von Hippel–Lindau (VHL) gene encodes a protein consisting of 213 amino acid residues with an apparent molecular mass of 30 kDa (pVHL(30)). Here we show that cells also produce a VHL protein (pVHL(19)) that appears to arise as a result of internal translation from the second methionine within the VHL ORF. pVHL(30) resides primarily in the cytosol, with less amounts found in the nucleus or associated with cell membranes. In contrast pVHL(19), in biochemical fractionation experiments, is equally distributed between the nucleus and cytosol and is not found in association with membranes. pVHL(19), like pVHL(30), can bind to elongin B, elongin C, and Hs-Cul2 in coimmunoprecipitation assays and can inhibit the production of hypoxia-inducible proteins such as vascular endothelial growth factor (VEGF) and GLUT1 when reintroduced into renal carcinoma cells that lack a wild-type VHL allele. Thus, cells contain two biologically active VHL gene products.